The impact of load bearing capacity of airfield pavement structures on the air traffic safety - Wesołowski, Mariusz; Blacha, Krzysztof (International Conference “Environmental Engineering”, 2017)
Airfield pavement is a marked and appropriately prepared surface of an airfield functional element that performs a definite function in aircraft operations. The structure of airfield pavement is most often composed of a set of layers whose task is to absorb and transfer loads coming from moving aircraft onto the ground in a way that ensures its definite durability. Structures of airfield pavements are designed for a definite exploitation period on the assumption of predicted volume and structure of the air traffic. Safety of air operations conducted by aircrafts on airfield pavements depends mainly on the state of bearing capacity of their construction. Due to the above, control tests of bearing capacity shall be periodically conducted, since information regarding the current state of an airfield pavement constitutes the basis for decisions concerning the types of aircrafts permitted to land and take off, traffic volume and dates of starting renovation or modernization works. In addition to loads generated by aircraft, on the condition of airfield pavement load bearing capacity is influenced by many external factors, including weather conditions. The ACN-PCN non-destructive method is currently used in the assessment of airfield bearing capacity, which has been introduced by ICAO (ICAO 2013). According to its assumptions, the airfield construction bearing capacity may be expressed in PCN or permissible number of air operations. The fundamental problem by measuring airfield pavements is to assume the correct computational model of a structure, which describes the way of cooperation and mechanical properties of individual layers. This paper contains the way of assessing and description of PCN as well as presentation of the possibility of expressing bearing capacity results by determination of permissible number of aircraft operations. There is also interrelation between PCN and the permissible number of aircraft operations presented in a graphic way.